Computer assisted positioning of the proximal segment after sagittal split osteotomy of the mandible: preclinical investigation of a novel electromagnetic navigation system - Nova, Igor; Kallus, Sebastian; Berger, Moritz; Ristow, Oliver; Eisenmann, Urs; Freudlsperger, Christian; Hoffmann, Jürgen; Dickhaus, Hartmut (Journal of cranio-maxillofacial surgery, 2017)
Introduction: Modifications of the temporomandibular joint position after mandible osteotomy are reluctantly accepted in orthognathic surgery. To tackle this problem, we developed a new navigation system using miniaturized electromagnetic sensors. Our imageless navigation approach is therefore optimized to avoid complications of previously proposed optical approaches such as the interference with established surgical procedures and the line of sight problem. Material and methods: High oblique sagittal split osteotomies were performed on 6 plastic skull mandibles in a laboratory under conditions comparable to the operating theatre. The subsequent condyle reposition was guided by an intuitive user interface and performed by electromagnetic navigation. To prove the suitability and accuracy of this novel approach for condyle navigation, the positions of 3 titanium marker screws placed on each of the proximal segments were compared using pre- and postoperative Cone Beam Computed Tomography (CBCT) imaging. Results: Guided by the electromagnetic navigation system, positioning of the condyles was highly accurate in all dimensions. Translational discrepancies up to 0,65 mm and rotations up to 0,38° in mean could be measured postoperatively. There were no statistically significant differences between navigation results and CBCT measurements. Conclusion: The intuitive user interface provides a simple way to precisely restore the initial position and orientation of the proximal mandibular segments. Our electromagnetic navigation system therefore yields a promising approach for orthognathic surgery applications.
Availabe online 17 February 2017
Gesehen am 30.07.2018